INTELLECTUALISM ABOUT KNOWLEDGE HOW AND SLIPS - Cathrine V. FELIX (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
This paper argues that slips present a problem for reductive intellectualism. Reductive intellectualists (e.g., Stanley and Williamson 2001; Stanley 2011, 2013; Brogaard 2011) argue that knowledge how is a form of knowledge that. Consequently, knowledge how must have the same epistemic properties as knowledge that. Slips show how knowledge how has epistemic properties not present in knowledge that. When an agent slips, she does something different from what she intended; nonetheless, the performance is guided by her knowledge how. This reveals a divide between the knowledge that actively guides behaviour: the knowledge how that the agent applies sub-consciously; and the knowledge how she intends to guide her behaviour in the first place, which she is under the illusion of acting on even as she slips. I argue that this divide between two levels of knowledge how operative in the slip case has no parallel when it comes to knowledge that. Therefore, knowledge how cannot be reduced to knowledge that.